Objectification in Moxie Film by Amy Poehler - Maharanny Setiawan Poetri; Tryana Tryana; Ratu Prayuana; Diyah Iis Andriani; Irfan Rifai (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The study entitled Objectification in Moxie film by Amy Poehler. This study aims to analyze the occurances of the issue of objectification that will be examined by using objectification theory, and feminism appoarch to overcome the issue. The object of this study is the film Moxie (2021) directed by Amy Poehler. The film tells the story about high schoolers rebelling the issues that experienced bycharacters related to the main character which is her friends. Thus, as the guidance, the writer applies ten notions of objectification theory by Tarasenko- Struc (2021). This study uses the qualitative method to present the findings in both essay and picture form by describing the narrative and cinematography elements. This study focuses on the action of objectification experienced by the main character as a witness and how does she deal with it. The results of the study are divided into two events. First, it depicts the occurances of objectification in the main character’s highschool, those are: instrumentality, denial of autonomi, inertness, denial of subjectivity, reduction to body, reduction to appearance, and silncing. Second, the main character’s reaction of the issue of objectification is in the form of rebellion based on solidarity and friendship and primacy concrete relationship.